Gestión de talento humano y su incidencia en el proceso comunicacional - motivacional de los colaboradores del gobierno autónomo descentralizado del cantón Mocache, período 2018 - 2019. plan de comunicación. - Portugal Candelario, Celia Alexandra (2021)
The current research project entitled MANAGEMENT OF HUMAN TALENT AND ITS IMPACT ON THE COMMUNICATIONAL - MOTIVATIONAL PROCESS OF THE EMPLOYEES OF THE AUTONOMOUS DECENTRALISED GOVERNMENT OF THE CANTON MOCACHE, PERIOD 2018 - 2019. COMMUNICATION PLAN had the general objective of evaluating the management of human talent and its impact on the communication-motivational process; it is also aimed at analysing the impact of motivation, establishing the communication process used and identifying the means and procedures of communication used by the management of human talent. The research used qualitative, quantitative and explanatory types of research, literature review of books, articles and scientific papers limited only to the direct relationship of the subject of study, research techniques such as observation, survey and interview factors that allowed to obtain direct information the variables studied used. The results showed that there is weak management of the internal communication process, the management of human talent does not have regulations that allow permanent recognition of the effort of the work done by employees, it was also found that there are failures in the motivation through communication. Therefore, it is proposed to implement a communication plan to keep staff informed about policies, guidelines that contribute to greater participation and motivation of staff to improve the working environment; the institution must invest in adaptations for implementing and visibility of tools such as communication mechanisms within the institution. Keywords: human talent management, communication, motivation, communication plan, local government.